A study on the status of myopia and pre-myopia among primary school students in different regions of Shaanxi Province, China - Wei, Dong; Yangbing, Li; Chengfei, Liu; Ye, Zhang; Zihao, Wang; Yanying, Li; Xiaokang, He; Kunlin, Fu; Zhaojiang, Du (Frontiers in Pediatrics, 2025)
ObjectiveThis cross-sectional study aimed to investigate the geographic disparities in myopia and pre-myopia prevalence among elementary school students across three distinct regions of Shaanxi Province (southern Hanzhong, Guanzhong, and northern Yulin) to inform region-specific myopia control strategies.MethodsFrom March to May 2024, we employed multistage cluster sampling to recruit 8,207 eligible students (2,724 southern Shaanxi, 2,761 Guanzhong, 2,722 northern Shaanxi) from 12 randomly selected primary schools. Comprehensive ophthalmic examinations including uncorrected visual acuity and non-cycloplegic autorefraction were conducted. Continuous variables were expressed as mean ± standard deviation, while categorical variables were analyzed using chi-square tests.ResultsAge-standardized myopia prevalence was highest in northern Shaanxi (48.02%), followed by central Shaanxi/Guanzhong (42.96%) and southern Shaanxi (30.43%). Gender disparities persisted across all regions, with female students exhibiting significantly elevated myopia rates (southern Shaanxi: 34.00% vs. 26.91%; Guanzhong: 48.02% vs. 37.99%; northern Shaanxi: 52.54% vs. 44.13%; P < 0.05 for all comparisons). Pre-myopia prevalence displayed an inverse geographic pattern (southern Shaanxi: 40.60% > Guanzhong: 34.19% > northern Shaanxi: 33.73%; χ2 = 185.3, P < 0.001), with male students consistently showing higher pre-myopia detection rates than females (southern Shaanxi: 42.45% vs. 38.73%; Guanzhong 38.28% vs. 30.01%; northern Shaanxi: 37.64% vs. 29.17%; P < 0.05). A marked grade-level progression was observed, with myopia prevalence increasing annually while pre-myopia rates declined significantly.ConclusionOur findings reveal a north–south gradient in ocular health outcomes, with northern Shaanxi demonstrating concerningly high myopia prevalence coupled with reduced pre-myopia detection rates. The persistent female predominance in myopia burden and early detection gaps underscores the need for gender-sensitive interventions. The observed progression patterns suggest critical windows for prevention, advocating for: (1) Preschool-initiated vision protection programs, (2) Establishment of digital refractive registries for high-risk cohorts, and (3) Implementation of regionally tailored myopia control protocols prioritizing northern districts.